Morgan Shuster and His Financial and Administrative Reforms in Iran 1911 - Albayati, Ahmed Kadhim Mohsin (Journal of Humanities & Social Sciences, 2019)
Morgan Shuster led a financial mission in Iran in 1911 and took several measures to tackle deteriorating financial conditions and almost achieved economic stability in the country. However, the influence of the external political factor did not exist, mainly from Russia, which was disturbed by the procedures of Shuster, as it saw its reforms as a threat to its influence in Iran. So, Russia worked hard to end the work of Shuster’s mission and used the threat, intimidation and issued an ultimatum to the Iranian government. After two days, when the parliament and the government rejected the Russian threat, the latter pushed its forces toward Iran and occupied some parts of the country, prompting the Iranian government to bow to Russian threats and end the mission in December 1911.
Keywords: Morgan Schuster; Iranian government; Russia